Effect of peripheral muscle fatigue during the testing of handgrip strength - Alex de Andrade Fernandes; Ciro José Brito; Breno Cesar Vieira; João Carlos Bouzas Marins
Introduction Muscle fatigue is a phenomenon associated with physical work. It is common in endurance sports, physical fitness tests and daily activities. Some tests can be directly affected by the effect of peripheral muscle fatigue, including the handgrip strength (HGS) test, which is considered baseline measure for assessing the functionality of the hand. Objectives a) verify the effect of peripheral muscle fatigue (between trials) during the testing of HGS, with a 60-second recovery interval; b) to analyze whether there is a difference in considering the mean value obtained in three trials or the best result as the final result. Materials and methods The final sample comprised 1,279 men. We followed the standard methodology and used a hydraulic hand dynamometer. Results There were statistically significant differences (P < 0.05) in the dominant hand among all the trials: first (46.5 ± 8.6 Kgf), second (46.4 ± 8.5 Kgf) and third (46.1 ± 8.6 Kgf); and also in the non-dominant hand: first (44.9 ± 8.4 Kgf), second (44.5 ± 8.3 Kgf) and third (44.0 ± 8.3 Kgf). We also found statistically significant differences (P < 0.05) between the two ways of considering the final result. For the dominant hand, the mean of the three attempts was 46.3 ± 8.3 Kgf and the best result was 48.1 ± 8.5 Kgf, whereas for the non-dominant hand, these results were 44.5 ± 8.2 Kgf and 46.0 ± 8.2 kgf, respectively. Conclusion Peripheral muscle fatigue directly interferes in the final result. A significant reduction in strength levels occurs in course of the assessment. The best result is frequently obtained at the first trial, which indicates that the highest value obtained should be considered as the final result.